An inter-laboratory assessment of the thorium isotopic composition of synthetic and rock reference materials - Sims, K; Gill, J; Dosseto, A; Hoffmann, D; Lundstrom, C; Williams, R; Ball, L; Tollstrup, D; Turner, S; Prytulak, J; Glessner, J; Standish, J; et al. (2008)
We present a concerted international effort to cross-calibrate five synthetic Th isotope reference materials (UCSC Th "A", OU Th "U", WUN, IRMM-35 and IRMM-36), and six rock reference materials (UCSC TML, Icelandic ATHO, USGS BCR-2, USGS W-2, USGS BHVO-2, LV18) using multi-collector inductively coupled plasma-mass spectrometry (MC-ICP-MS). We then compare our new values with a compilation of literature mass spectrometric data for these reference materials and derive recommended "consensus" 230Th/232 Th values for each. We also present isotope dilution U and Th concentration data for four rock reference materials (UCSC TML, Icelandic ATHO, USGS BCR-2, USGS W-2). © 2008 International Association of Geoanalysts.